The Effect Of Sales Growth, Profitability And Tax Planning On The Value Of The Company - Vianty Adella Santo; I Gusti Agung Musa Budidarma; Melody Natashia Sandiputri (Balance Vocation Accounting Journal, 2026)
This study aims to examine the effect of sales growth, profitability, and tax planning on firm value in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange during the period 2021–2024. Firm value is measured using Tobin’s Q, sales growth is proxied by Sales Growth, profitability is measured by Return on Assets (ROA), and tax planning is measured using the Tax Retention Rate (TRR). This research employs a quantitative approach using secondary data derived from companies’ annual reports. The sampling technique used purposive sampling, resulting in 53 companies with a total of 212 observations. Panel data regression analysis was conducted using Eviews 13, and the Random Effect Model was selected as the best model. The results indicate that sales growth does not have a significant effect on firm value. Meanwhile, profitability has a positive and significant effect on firm value. Conversely, tax planning has a negative and significant effect on firm value.